2018
DOI: 10.1101/500595
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes and practices regarding rabies and its control among dog owners in Kigali city, Rwanda

Abstract: Background: Rabies is a zoonotic viral disease that can occur in all warm-blooded mammals, including man [1]. Vaccinating dogs can protect people from contracting rabies [2]. Annual deaths due to rabies was estimated to 61000 worldwide [1], and Africa represented 35.2% of the deaths [3]. In Rwanda, rabies is a public health threat to the public [4], but the country does not have information on the disease [5]. Methodology: The present study aimed to assess knowledge, attitudes and practices (KAP) of rabies and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
3
4
2
Order By: Relevance
“…This also applies to the Nepalese context. Our study further tied well with the findings of Ntampaka et al [24]. They also reported similar observations that the higher level of education might have helped participants to understand the treatment methods and their availability in their area.…”
Section: Knowledgesupporting
confidence: 92%
See 1 more Smart Citation
“…This also applies to the Nepalese context. Our study further tied well with the findings of Ntampaka et al [24]. They also reported similar observations that the higher level of education might have helped participants to understand the treatment methods and their availability in their area.…”
Section: Knowledgesupporting
confidence: 92%
“…However, a limited number of respondents preferred to consult the local healer and applied the herbal products and spices as a substitute for the first aid. Washing the dog bite wound with soap water has been strongly recommended [1] Nepalese participants' response was relatively better than the previous reports found in Rwanda, Tanzania, and India, Rwanda (20.4%), Tanzania (5%), and India (43.07%) [24,25,35]. Therefore, the study suggested that awareness and educational programs were required in the communities to control rabies.…”
Section: Attitude and Practicementioning
confidence: 85%
“…In contrast, pet owners did not employ adequate practises for the vaccination of their pets. These findings were inconsistent with Ntampaka et al [ 30 ] study in Rwanda who reported that 58% owners had their pets vaccinated at least once a year. This might be due to socio-economic variation with Bangladesh and indicates lack of best practices that need to be improved through awareness campaigns.…”
Section: Discussioncontrasting
confidence: 76%
“…The success of the One Health initiative relies on enhancing the KAP level among the public and on improving the skill of the personnel directly dealing with animal bite management and suspected rabies patients, including humans and animals. There have been many community-based rabies surveys that have focused only on the community members in Bangladesh and other developing countries [ [22] , [23] , [24] , [25] , [26] , [27] , [28] ]; however, till date no study in Bangladesh and a minimum number of studies in elsewhere have determined the level of KAP about rabies among other stakeholders of rabies elimination programme [ [29] , [30] , [31] , [32] ].…”
Section: Introductionmentioning
confidence: 99%
“…We determined the sample size based on the national dog population of 18,117 reported in 2016 [28]. The number of dogs in Kigali represented 2,157, thus 11.9% of the national dog population [29]. Due to a lack of previous studies on canine helminthiases in Rwanda, the prevalence of canine nematodiases was assumed to be 50%.…”
Section: Study Design and Sample Sizementioning
confidence: 99%